2009
DOI: 10.3109/08860220903137509
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline in Ischemia-Induced Acute Kidney Injury in Rats

Abstract: Ischemia is an important cause of acute kidney injury (AKI). Pentoxifylline has been shown to improve tissue oxygenation and endothelial function and inhibit proinflammatory cytokine production. The aim of this study was to evaluate a possible renal protective effect of pentoxifylline against ischemia by measuring mitochondrial respiratory metabolism as an index of cell damage. Rats were submitted to right nephrectomy. The left kidney was submitted to ischemia by clamping the renal artery for 45 minutes. Immed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
1
6
1
1
Order By: Relevance
“…In this context, mycophenolate mofetil has recently been reported to reduce expression of the monocyte Toll-like receptor 4 and improve the course of IRI and iAKI in mice when given for 2 days before renal ischemia [20]. Of note, in compliance with our results, Okumura et al [21] showed no nephroprotective effect of PTX in the model of iAKI in rat when the drug was administered during reperfusion of the ischemic kidney.…”
Section: Discussionsupporting
confidence: 88%
“…In this context, mycophenolate mofetil has recently been reported to reduce expression of the monocyte Toll-like receptor 4 and improve the course of IRI and iAKI in mice when given for 2 days before renal ischemia [20]. Of note, in compliance with our results, Okumura et al [21] showed no nephroprotective effect of PTX in the model of iAKI in rat when the drug was administered during reperfusion of the ischemic kidney.…”
Section: Discussionsupporting
confidence: 88%
“…32 PTX has been shown to improve tissue oxygenation and endothelial function and to inhibit proinflammatory cytokine production. 8 In the present study, PTX improved tissue oxygenation by a reduction in oxidative stress but this was not sufficient for preservation of renal function. Although downregulation of proinflammatory cytokines seems to be important for the protection or attenuation of injury it is possible that mitochondria were already highly damaged by the ischemic process.…”
Section: Discussioncontrasting
confidence: 61%
“…8 PTX also inhibits cell proliferation and extracellular matrix accumulation. Human studies have proved its antiproteinuric effect in patients with glomerular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…It can also affect the microcirculatory blood flow and contribute to the attenuation of interstitial inflammation, down regulation of monocyte chemo-attractant protein-1 gene expression, reduction in the expression of mitogenic and profibrogenic genes, and suppression of the proliferation of interstitial fibroblast and glomerulomesangial cells [8]. However, the preclinical data with regard to PTX and AKI seems controversial [9,10]. The effect of PTX in reducing renal injury by measuring sCr and α-1-microglobulin was investigated and ameasuring sCr and beneficial role of PTX on the prevention of kidney injury was observed [11].…”
Section: Introductionmentioning
confidence: 99%